Капсульний гардероб як інструмент зменшення обсягів текстильних відходів - Адашевський, Н. О.; Крючкова, Валерія Валеріївна (ГО "Міжнародна наукова гільдія", 2026)
This paper presents the results of a study investigating the factors influencing the limited adoption of capsule wardrobes among teenagers. Adopting the capsule wardrobe method to compile everyday outfits is a form of conscious consumption that can significantly reduce clothing waste, which turns into textile waste within a year or two. The study found that the lack of capsule wardrobe idea promotion in social media is one of the most important limiting factors.
Keywords: капсульний гардероб; текстиль; текстильні відходи; мода; одяг; нардероб